2017
DOI: 10.1259/bjr.20160918
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of stereotactic cone size and detector specific output correction factor

Abstract: The use of small photon fields in radiotherapy techniques has increased substantially due to the wider clinical implementation of stereotactic radiosurgery (SRS), stereotactic body radiotherapy and intensity modulated radiotherapy. Accuracy of dose delivery from such special techniques is largely dependent on the accuracy of beam data commissioned in the treatment planning system (TPS). The commissioning of TPS with incorrectly measured or extrapolated beam data, specially nominal output and field output facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
7
3
Order By: Relevance
“…The daisy-chain method mitigates this effect by normalizing to an intermediate field size (e.g., 4 × 4 cm 2 ) using two different detectors (a diode and an ion chamber). Sharma et al reported up to −5% variation of OFs for the Edge detector when OFs measured using the daisy-chain method were compared with OFs directly normalized to a field size of 10 × 10 cm 2 for cones [22]. In our study, the OF difference between with and without the daisy-chain method for cones was less than 1% and OFs were underestimated without the daisy-chain method.…”
Section: Measurementscontrasting
confidence: 43%
“…The daisy-chain method mitigates this effect by normalizing to an intermediate field size (e.g., 4 × 4 cm 2 ) using two different detectors (a diode and an ion chamber). Sharma et al reported up to −5% variation of OFs for the Edge detector when OFs measured using the daisy-chain method were compared with OFs directly normalized to a field size of 10 × 10 cm 2 for cones [22]. In our study, the OF difference between with and without the daisy-chain method for cones was less than 1% and OFs were underestimated without the daisy-chain method.…”
Section: Measurementscontrasting
confidence: 43%
“…In small fields, an additional opposing effect is due to the presence of silicon, which introduces an over-response in small fields due to a fluence perturbation that is not negligible. 146,147 A possible solution is to use the intermediate field method, sometimes referred to as the daisy chain technique [148][149][150] (cross calibration of diode against the chamber in an intermediate field to connect measurements in large fields to small fields) to measure field output factors normalized to a 10 cm 2 × 10 cm 2 field. Although this technique accounts for the energy dependence of large fields, it does not consider the electron fluence perturbation due to the high density of silicon in small fields.…”
Section: Solid-state Detectorsmentioning
confidence: 99%
“… For fields less than 1 cm × 1 cm, the interplay of source occlusion and detector choice demands precise positioning of the detector. The resolution of the scanning measurement should be smallest possible to the limit of device usually 0.1 mm. Dosimetric measurements should be performed with more than one detector system. Strategies to minimize variations in measurements among users should be tested, utilized, and shared The daisy chain approach 148‐150,322 can be used to determine output factors for the complete range of field sizes needed clinically. However, it should be remembered that this method normalizes the response increase in large fields, it does not account for the fluence perturbation effect that may require a correction.…”
Section: Key Recommendations and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the complex issues involving small field mentioned above could also lead to incorrect calculations of absorbed dose in treatment planning systems (TPS), 2 due to simplifications in the modeling of the lateral electron scattering or using extrapolated beam data for small fields, 3,4,[8][9][10] with the inaccuracies mostly prominent in highly heterogeneous cases such as in the thorax.…”
Section: Introductionmentioning
confidence: 99%